PERBANDINGAN EFEKTIFITAS PENURUNAN KADAR BOD DAN COD PADA LIMBAH CAIR INDUSTRI TAHU MENGGUNAKAN TANAMAN KAYU APU (Pistia stratiotes) DAN TANAMAN ECENG GONDOK (Eichornia crassipes Solms) - Enggrit Ariana Sari; Koerniasari .; Soekiran Al Jauhari (Poltekkes Kemenkes Surabaya, 2016)
Tofu waste is the waste generated in tofu manufacturing process. The Waste is generated in the form of solid and liquid wastes. The liquid waste contains organic material. When it is disposed in water without processing, it will cause pollution, such as the reduction of oxygen dissolved in the water causing disturbance on organisms living in the water. This is an actual experimental research by using